Research Progress on the Treatment of Benign Prostatic Hyperplasia with Classical Prescriptions - Zhang, Lin; Wang, Yang; Liu, Mingze; Wang, Zhenliang (Chinese medicine and natural products, 2024)
The main pathogenesis of benign prostatic hyperplasia (BPH) includes deficiency of healthy qi, blood stasis, and fluid retention. The root cause of BPH is the deficiency of healthy qi, for which Jingui Shenqi Pill and Zhenwu Decoction are used to nourish kidney qi and warm yang to promote diuresis. Blood stasis is the key pathogeneses of BPH, for which Guizhi Fuling Pill and Didang Decoction are used to dissipate blood stasis, relieve obstruction of orifices and facilitate bowel movement. Fluid retention is the most urgent symptom of BPH, for which Wuling Powder and Danggui Shaoyao Powder are used to transform qi and promote diuresis, addressing the urgent symptoms.
Keywords: benign prostatic hyperplasia; Jingui Shenqi Pill; Zhenwu Decoction; Guizhi Fuling Pill; Didang Decoction; Wuling Powder; Danggui Shaoyao Powder